Studi Literatur Komitmen Akuntan Terhadap Profesinya - Manatap Berliana Lumban Gaol; Adanan Silaban (Jurnal Akuntansi dan Pajak, 2023)
The accounting profession is a profession that provides services to protect the public interest. Therefore, every accountant must have the responsibility to maintain and respect his profession. The accountant's commitment to his profession is a form of individual loyalty to his profession and relates performance to his performance. This article aims to describe and theoretically develop the accountant's commitment to his profession. To achieve this goal, a review of previous research was carried out in the accounting profession and other professions. Based on the literature review, it shows empirical evidence of the existence of multi-dimensional professional commitment in various professions, and finds that each dimension relates differently to affect and behavior. However, most of the research on the commitment of accountants to their profession is still unidimensional. Opportunities for future research, namely the relationship between the dimensions of the commitment of accountants to their profession with the antecedents and their consequences are stated.